Refusal Strategies of Iranian EFL Learners: the role of sex, age, education levels and politeness - Parvaresh, Hamid Reza; Khomeijani Farahani, Ali Akbar (International Journal of Education and Cognitive Sciences, 2022)
Introduction: The current study aimed at finding if there is any significant difference between male and female participants in the type of refusal strategies they use across different age and education levels as well as politeness systems. Materials and method: 110 Persian native speakers, 48 male and 42 female took a Discourse Completion Test (DCT) which included 8 scenarios in each of which the respondents were presented with a situation in which they had to respond to a stimulus by rejecting it. The answers given to each item were analyzed and coded by an expert in pragmatics based on the taxonomy employed by Beebe, Takahashi and Uliss-Weltz (1990). To investigate the first research questions a series of Mann-Whitney U Test was used. Also, to investigate the effect of age (the second research question), educational background (the third research question), and the politeness system (the fourth research question) on the use of refusal strategies, three sets of Kruskal-Wallis H Tests were carried out using SPSS. Results: Based on the results obtained, male and female participants were found to differ significantly only in their use of the ‘regret’ type of refusal strategies. A significant difference was observed among the age groups, different educational backgrounds and different politeness systems.Conclusion: There are significant differences in refusal strategies based on gender, age, educational backgrounds and politeness systems.